Modern Approaches to the Technology of Tablet Dosage Forms of Thioctic Acid (Review) - S. N. Egorova; I. V. Bulygina; N. V. Vorobeva; D. P. Chuvashova; N. R. Mustafina (Разработка и регистрация лекарственных средств, 2021)
Introduction. Thioctic (α-lipoic) acid is an endogenous antioxidant and is used for liver diseases, poisoning with salts of heavy metals, hyperlipidemia, atherosclerotic heart disease, neuropathy, insulin-resistant forms of diabetes mellitus, etc. technologies for producing tableted medicinal preparations of thioctic acid, necessary for the pharmaceutical development of thioctic acid tablets at pharmaceutical industry enterprises.Text. The review considers the physicochemical properties of the pharmaceutical substance thioctic acid, the features of its pharmaceutical and technological properties, and compatibility with excipients. In the technology of thioctic acid tablets, methods of direct compression and compression with preliminary wet granulation, including those using organic solvents, are used. To increase photostability, thioctic acid tablets are coated. Information on excipients in the composition of core tablets and film coat of thioctic acid tablets registered in Russia is presented. The problems of tabletting thioctic acid are described: sintering of the granulate during the drying process, adhesion of the tabletting mass to the pressing tool and the resulting unevenness of the tablet surface. The ways of optimizing the tabletting process of thioctic acid using various compositions of excipients, improving the flowability of a pharmaceutical substance both during its synthesis and as a result of technological processing, choosing the optimal modes of granulation, drying, pressing are considered.Conclusion. As a result of the analysis of the literature data, the features of the technology for producing thioctic acid tablets were revealed, which are due to the high content of the pharmaceutical substance in tablets (up to 600 mg), the need to use a minimum amount of excipients (from 27 to 51 %), poor flowability, and low melting point of the pharmaceutical substance. Improvement of compressibility and prevention of adhesion can be achieved by using the pharmaceutical substance thioctic acid of a certain granulometric composition, auxiliary substances of the basic nature and a high content of glidants (up to 6 %). The identified manufacturing features should be taken into account in the pharmaceutical development of thioctic acid tablets.